2020
DOI: 10.1037/ccp0000465
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ behaviors and youths’ therapeutic alliance during trauma-focused cognitive behavioral therapy.

Abstract: Objective: Trauma-focused cognitive-behavioral therapy (TF-CBT) is a recommended treatment for posttraumatic stress (PTS) in youth, and a strong therapeutic alliance predicts reductions of PTS in TF-CBT. However, little is known of how therapists can build a strong alliance. This study seeks to understand which therapist behaviors are associated with the strength of alliance in TF-CBT. Method: Participants were 65 youth (M age ϭ 15.1, SD ϭ 2.19; 77% girls) engaged in TF-CBT and their therapists (n ϭ 24). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…The majority of studies, which mostly investigated adult patients, report moderate therapist effects of approximately 5% (Johns et al, 2019 ), but the overall range of therapist effects is relatively large and varies from 0.2% to 48.7% (Crits-Christoph et al, 1991 ; Crits-Christoph & Mintz, 1991 ; Johns et al, 2019 ; Lutz, Leon, Martinovich, Lyons, & Stiles, 2007 ). Frequently researched therapist variables are the therapists’ theoretical background/orientation (Anderson, Ogles, Patterson, Lambert, & Vermeersch, 2009 ; Berglar et al, 2016 ; Okiishi et al, 2006 ), professional interpersonal skills or self-rated professional characteristics (Heinonen & Nissen-Lie, 2019 ), therapists’ alliance-building behaviours (Jungbluth & Shirk, 2009 ; Ovenstad, Ormhaug, Shirk, & Jensen, 2020 ), professional experience (e.g. years of experience doing therapy; Huppert et al, 2001 ; Turner, Nicholson, & Sanders, 2011 ), age (Anderson et al, 2009 ; Schauenburg, Dinger, & Strack, 2005 ) and gender (Shiner, Westgate, Harik, Watts, & Schnurr, 2017 ; Zorzella, Muller, & Cribbie, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies, which mostly investigated adult patients, report moderate therapist effects of approximately 5% (Johns et al, 2019 ), but the overall range of therapist effects is relatively large and varies from 0.2% to 48.7% (Crits-Christoph et al, 1991 ; Crits-Christoph & Mintz, 1991 ; Johns et al, 2019 ; Lutz, Leon, Martinovich, Lyons, & Stiles, 2007 ). Frequently researched therapist variables are the therapists’ theoretical background/orientation (Anderson, Ogles, Patterson, Lambert, & Vermeersch, 2009 ; Berglar et al, 2016 ; Okiishi et al, 2006 ), professional interpersonal skills or self-rated professional characteristics (Heinonen & Nissen-Lie, 2019 ), therapists’ alliance-building behaviours (Jungbluth & Shirk, 2009 ; Ovenstad, Ormhaug, Shirk, & Jensen, 2020 ), professional experience (e.g. years of experience doing therapy; Huppert et al, 2001 ; Turner, Nicholson, & Sanders, 2011 ), age (Anderson et al, 2009 ; Schauenburg, Dinger, & Strack, 2005 ) and gender (Shiner, Westgate, Harik, Watts, & Schnurr, 2017 ; Zorzella, Muller, & Cribbie, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since most of the studies on the role of therapists are conducted with adult samples, little is known about therapist effects in psychotherapy with children and adolescents (Fjermestad, McLeod, Tully, & Liber, 2016 ). So far, only preliminary results on single factors such as therapists’ relationship skills (Alexander, Barton, Schiavo, & Parsons, 1976 ), therapists’ alliance building behaviours (Jungbluth & Shirk, 2009 ; Ovenstad et al, 2020 ) or ethnicity and language of the therapist are available (Halliday-Boykins, Schoenwald, & Letourneau, 2005 ; Yeh, Eastman, & Cheung, 1994 ). A study by Wintersteen, Mensinger, and Diamond ( 2005 ) found that ‘same gender’ matched dyads of therapists and patients in the treatment of 600 adolescent substance abusers reported higher alliance ratings and that the patients were more likely to complete treatment compared with ‘different-gender’ dyads.…”
Section: Introductionmentioning
confidence: 99%
“…With the majority of young people admitted to acute inpatient units having a history of trauma, therapeutic touch could be viewed as either detrimental or helpful. Some adolescents may experience PTSD trigger type responses, while others may feel comforted, and potentially learn to trust adults (Ovenstad et al, 2020). Further research into the acceptance and effectiveness of therapeutic touch for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Integral to all nursing interventions in an acute inpatient unit is the therapeutic alliance and relationships that nurses can establish, maintain and repair with the young people for whom they provide care. Many young people admitted to acute inpatient units have experiences of childhood trauma and attachment disruption, and these experiences impact the young person's beliefs of adult helpfulness and trust (Ovenstad et al, 2020). Establishing therapeutic relationships with adolescents in the inpatient setting requires nurses to have specialist interpersonal communication skills and to consider the developmental factors associated with the child and adolescent mental health population (Delaney, 2017; Engstrom et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therapists' observed in-session behavior could be an important contributor to the alliance, as has been shown in several studies in individual youth therapy (Creed & Kendall 2005;Fjermestad et al, 2020;Ovenstad et al, 2020). For conjoint family treatment however, studies on alliance building behaviors are scarce.…”
Section: Therapists' Alliance Building Behaviorsmentioning
confidence: 99%